Treatment with combined exercise in patients with resistant major depression (TRACE-RMD): study protocol for a randomised controlled trial - Nagore Iriarte-Yoller; José Etxaniz-Oses; Cristobal Pavón-Navajas; Mikel Tous-Espelosin; Pedro M. Sánchez-Gómez; Sara Maldonado-Martín; Ana B. Yoller-Elburgo; Edorta Elizagarate-Zabala (Trials)
Abstract Background Around 40% of people with major depressive disorder (MDD) experience moderate remission, with the remainder meeting the criteria for resistant major depression (RMD). It has been shown that exercise has a low-to-moderate effect on MDD, but there is a lack of evidence on exercise interventions in RMD patients. The primary purpose of the proposed study will be to investigate the effect of a 12-week supervised combined exercise program on depressive symptoms in people with RMD compared to a treatment-as-usual (TAU) group. Method This randomised, single-blind, controlled experimental trial will include 70 adults (≥ 18 years old) with RMD. Participants randomised to an exercise intervention, or a TAU group will be assessed at baseline and after a three-month intervention period. The primary variable will be participants’ depressive symptoms measured with the Montgomery-Asberg Depression Rating Scale. Secondary outcome variables will include cardiorespiratory fitness (peak oxygen uptake through peak cardiopulmonary exercise test), body composition (bioimpedance and anthropometric variables), physical activity level (the International Physical Activity Questionnaire), health-related quality of life (the Short Form-36 Health Survey), functional outcome (the Sheehan Disability Scale and Quality of Life in Depression Scale), overall disease severity (the Clinical Global Impression Scale-Severity of Illness), and biochemical variables (a fasting blood sample). Discussion This study will try to answer whether a supervised co-adjuvant combined (aerobic and resistance training) exercise program will help the prognosis of this population with RMD. Trial registration ClinicalTrials.gov NCT05136027. Last public release on 12/13/2023.